New questions and answers about dinosaurs - Simon, Seymour; Dewey, Jennifer (New York : Morrow Junior Books, 1990)
Explores new discoveries about dinosaurs and answers such questions as "Were all dinosaurs giants?" "How are dinosaurs named?" "Which was the largest meat-eater?" and "How smart were the dinosaurs?".
Includes index.
Booklist.
School Library Journal.
Wilson's Children.
4.5
4.5
Keywords: Dinosaurs -- Miscellanea -- Juvenile literature; Dinosaurs; Questions and answers; Dinosaurs; Questions and answers